Characteristics of cataract patients who underwent cataract surgery in H. L. Manambai Abdulkadir hospital Sumbawa - Paramita, Anak A. D.; Wibowo, Aloysius A.; Warnerin, Eka B. P. (International Journal of Research in Medical Sciences, 2024)
Background: Cataract is a clouding of the natural intraocular crystalline lens that can cause decrease in vision and may lead to blindness. Worldwide, cataracts are number one cause of preventable blindness. Cataract surgery is the most effective intervention regardless of its etiology. The purpose of this study was to obtain characteristics of cataract patients who underwent cataract surgery in H. L. Manambai Abdulkadir hospital Sumbawa based on cataract types, sex, age, comorbidities, initial visual acuity, and surgery methods. Methods: A quantitative study at H. L. Manambai Abdulkadir hospital Sumbawa. Consecutive, non-random sampling technique was used to recruit participants. This study enrolled 317 cataract patients who underwent cataract surgery. Results: Of the 317 patients, 172 (54.26%) were men, 301 (94.95%) senile cataract, 141 (44.48%) bilateral case, 210 (66.25%) initial visual acuity <3/60, 43 (13.56%) with diabetes mellitus. Two hundred and seventy eight (88.54%) underwent phacoemulsification surgery, with 303 (95.58%) experienced visual acuity improvement. Conclusions: Most of cataracts patients who underwent cataract surgery were men, most surgery were done by phacoemulsification method. Senile cataract and bilateral case are the most common case. Patients had visual acuity improvement after cataract surgery.